The sight : a novel - Golding, Melanie (Crooked Lane, 2023)
"As a child, Faith acquired the ability to see when and how people would die--a "gift" she neither wanted nor could get rid of. After foreseeing a family tragedy and being ostracized, Faith learns to control her visions, and returns to perform in her family's traveling carnival. But when an unruly customer attacks her, she has a vision in full view of a crowd. She is banned from the carnival she loves--and loses her only source of income to support her dying mother. Desperate to support her mother and with only one friend standing by her, she sees no reason to continue hiding her ability and goes to dangerous lengths to earn money. But when she sees herself in a man's future death, Faith must face her own fears of her powers and tune into her gift to fight against a future that would ruin her life--and end someone else's" --